Hymenobacter caeli sp. nov., an airborne bacterium isolated from King George Island, Antarctica - Roldán, Diego M; Kyrpides, Nikos; Woyke, Tanja; Shapiro, Nicole; Whitman, William B; Králová, Stanislava; Sedláček, Ivo; Busse, Hans-Jürgen; Menes, Rodolfo Javier (International journal of systematic and evolutionary microbiology, 2021)
A rod-shaped and Gram-stain-negative bacterial strain 9AT, was isolated from an air sample collected at King George Island, maritime Antarctica. Phylogenetic analysis based on 16S rRNA gene sequence reveals that strain 9AT belongs to the genus Hymenobacter and shows the highest similarity to Hymenobacter coccineus CCM 8649T (96.8 %). The DNA G+C content based on the draft genome sequence is 64.9 mol%. Strain 9AT is strictly aerobic, psychrophilic, catalase-positive, oxidase-positive and non-motile. Growth is observed at 0-20 °C (optimum 10 °C), pH 6.0-8.0 (optimum pH 7.0), and in the absence of NaCl. The predominant menaquinone of strain 9AT is MK-7 and the major fatty acids comprise Summed Feature 3 (C16 : 1 ω7c and/or C16 : 1 ω6c; 25.2 %), iso-C15 : 0 (23.2 %), C16 : 1 ω5c (11.6 %), Summed Feature 4 (anteiso-C17 : 1 B/iso-C17 : 1 I) (9.6 %) and anteiso-C15 : 0 (9.6 %). The polar lipid profile consists of the major lipid phosphatidylethanolamine and moderate to minor amounts of phosphatidylserine, unidentified aminolipids, aminophospholipids, aminophosphoglycolipids, polar lipids lacking a functional group and an unidentified phospholipid and a glycolipid. In the polyamine pattern sym-homospermidine is predominant. On the basis of the results obtained, strain 9AT is proposed as a novel species of the genus Hymenobacter, for which the name Hymenobacter caeli sp. nov. is suggested. The type strain is 9AT (=CCM 8971T=LMG 32109T=DSM 111653T).
Keywords: maritime Antarctica; extremophiles; mikrobiologie vzduchu; DNA bakterií; RNA, Ribosomal, 16S; DNA, Bacterial; pravděpodobnostní funkce; Bacteroidetes; Genome, Bacterial; airborne bacteria; genom bakteriální; Air Microbiology; zastoupení bazí; ostrovy; Likelihood Functions; Phylogeny; Hymenobacter sp.; Islands; Antarktida; Antarctic Regions; psychrophiles; Base Composition; fylogeneze; RNA ribozomální 16S